Diamond Creek - Emergency Supplemental Funds - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2011)
Located in: Fort Collins office files. Robert Emrick's Diamond Creek records related Colorado State Forest Service (CSFS) Emergency Supplemental Funds (ESF) programs. Includes: grant application; program application; payment requests; accomplishment reports for reimbursement; invoices; cost documentation; annotated maps; photographic prints; and correspondence.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado